Diurnal profiles of salivary cortisol on workdays among construction workers versus white-collar workers - Hansen, Åse Marie; Persson, Roger; Garde, Anne Helene; Karlson, Björn; Ørbæk, Palle (SJWEH Supplements, 2006)
' ' OBJECTIVES ': 'The aim of the present study was to test whether construction workers, who are known to have a relatively higher risk of cardiovascular disease (CVD), had higher concentrations of cortisol in saliva and a lower relative variability when compared with white-collar workers. ' ' METHODS ': 'Data from two groups of male construction workers with physically demanding job assignments, with either regular or extended workhours (N=40) and a group of white-collar workers recruited from both the private and the public sector (N=118) were examined. All of the workers had participated in previous research projects with similar methodology. Saliva was sampled during ordinary workdays at awakening, between 30 and 45 minutes after awakening, and approximately 14 hours after awakening. ' ' RESULTS ': 'Compared with the white-collar workers, the construction workers had higher mean concentrations of cortisol in saliva, 36% and 14% for construction workers with regular and extended workhours, respectively. The observed differences weakened when the exact sampling time (time of day) was taken into consideration in the statistical modeling. Compared with the white-collar workers, the construction workers had a lower relative variability in salivary cortisol as measured by the coefficient of variation (CV 76% versus 99%). A detailed analysis revealed that the construction workers with regular workhours had the highest concentration of cortisol in saliva but the lowest relative variability when compared with the construction workers with extended workhours (CV 72% versus 82%). ' ' CONCLUSIONS ': 'The results suggest that physically demanding construction work is associated with a less variable and increased cortisol excretion when compared with white-collar work.
Keywords: cardiovascular disease; construction worker; diurnal profile; hypothalamus-pituitary-adrenal axis; radioimmunoassay; salivary cortisol; white-collar worker; workday; worker; workhours